Relaksasi Otot Progresif Meningkatkan Kualitas Tidur pada Lansia Wanita - Putu Agus Ariana; G. Nur Widya Putra; Ni Komang Wiliantari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the effectiveness of progressive muscle relaxation to improve sleep quality in the elderly who has insomnia in the Unggahan Village, Buleleng Regency. This research method is a quantitative study with a pre experiment research design with one group design pre-post test design. The results showed statistically, progressive muscle relaxation was effective to improve sleep quality in elderly women with a value of p = 0,000 or p <Î± (0.05). Conclusion, progressive muscle relaxation is effective in increasing sleep quality in the elderly who live at home. Keywords: Sleep Quality, Elderly, Progressive Muscle Relaxation